2015
DOI: 10.1073/pnas.1319378112
|View full text |Cite
|
Sign up to set email alerts
|

i/o -coupled receptor signaling restricts pancreatic β-cell expansion

Abstract: Gi-GPCRs, G protein-coupled receptors that signal via Gα proteins of the i/o class (Gαi/o), acutely regulate cellular behaviors widely in mammalian tissues, but their impact on the development and growth of these tissues is less clear. For example, Gi-GPCRs acutely regulate insulin release from pancreatic β cells, and variants in genes encoding several Gi-GPCRs—including the α-2a adrenergic receptor, ADRA2A—increase the risk of type 2 diabetes mellitus. However, type 2 diabetes also is associated with reduced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(68 citation statements)
references
References 64 publications
3
64
1
Order By: Relevance
“…As GPCRs have been described to contribute to β cell mass through their role in mediating β cell properties such as proliferation and apoptosis1314151617181920, we examined the effect of Ffar2 deletion on β cell mass. Immunohistochemical (IHC) and morphometric analysis of normal chow (NC) fed Ffar2 −/− male mice at 26 weeks revealed significantly decreased insulin positive area (relative to total pancreatic area), smaller average β cell area per islet, and decreased β cell mass compared to age matched, WT controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As GPCRs have been described to contribute to β cell mass through their role in mediating β cell properties such as proliferation and apoptosis1314151617181920, we examined the effect of Ffar2 deletion on β cell mass. Immunohistochemical (IHC) and morphometric analysis of normal chow (NC) fed Ffar2 −/− male mice at 26 weeks revealed significantly decreased insulin positive area (relative to total pancreatic area), smaller average β cell area per islet, and decreased β cell mass compared to age matched, WT controls (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Compromised β cell development in rats results in an insufficient number of cells to adequately control glucose metabolism (Figliuzzi et al, 2010). In mice, perinatal β cell proliferation rates can be tuned via the modulation of Gi-GPCR signaling (Berger et al, 2015). Changes to early β cell proliferation capacity in these mice correlates directly with adult β cell mass, which subsequently impacts glucose regulation (Berger et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…In mice, perinatal β cell proliferation rates can be tuned via the modulation of Gi-GPCR signaling (Berger et al, 2015). Changes to early β cell proliferation capacity in these mice correlates directly with adult β cell mass, which subsequently impacts glucose regulation (Berger et al, 2015). Furthermore, meta analysis of human data has revealed a correlation between an early age of β cell loss and more rapid onset of T1D (Klinke, 2008), consistent with the model that failure to generate a reserve of β cells early in development increases disease risk.…”
Section: Discussionmentioning
confidence: 99%
“…As with GSIS, Gα q/11 coupled GPCRs have been observed to augment β cell mass expansion in response to insulin resistance, whereas Gα i/o coupled GPCRs have been reported to restrict the β cell mass expansion [34, 35]. Not surprisingly, McNelis et al [19] observed reduced β cell mass in Ffar2 −/− mice on a HFD compared to WT mice, lower β cell proliferation and reduced expression of insulin and the β cell transcription factors ( Mafa , Pdx1 , NeuroD ) [19].…”
Section: Nutrient Sensing Receptorsmentioning
confidence: 99%